New-onset severe Diabetic Ketoacidosis in a 13-months old Nepali Toddler: a case report - Basnet, Bijay; Bhattarai, Chaitanya Darshan; Bhatt, Rohit; Chimoriya, Romila; Adhikari, Kushal; Yadav, Birendra Kumar (Nepal Medical College Journal, 2023)
Diabetes mellitus (DM) is a glucose metabolism disorder with diabetic ketoacidosis (DKA) being the most common complication associated with significant morbidity and mortality. Unlike other patients with typical symptoms of abdominal discomfort, pain, nausea and emesis of DKA, our patient presented with atypical symptoms such as cough, runny nose and fast breathing. This symptoms would have initially misled with diagnosis of respiratory tract infection, which would have caused delay in the treatment of DKA. In our patient DKA was treated with intravenous fluid replacement followed by intravenous insulin infusion, along with monitoring of blood glucose and electrolyte levels. We would like to emphasize that DKA can be precipitated by simple upper respiratory tract infection in toddlers with undiagnosed type 1 DM. Hence, random blood sugar measurement and urine for ketone bodies test should be performed if feasible in sick patients presenting with respiratory tract illness-like symptoms.